Case Report: A novel missense variant in ZC4H2, c.196C>T p.(Leu66Phe), is associated with a mild, ZC4H2-related X-linked syndromic intellectual disability (ZARD) phenotype - Ria Garg; Ria Garg; Wenying Zhang; Wenying Zhang; Julianne E. Hartmann; Anne Slavotinek; Anne Slavotinek (Frontiers in Pediatrics)
ZC4H2 is an X-linked gene that has emerged as critical for neural development, synaptic functioning, and gene regulation. We present an 11-month-old male who was evaluated for bilateral congenital vertical talus identified in the newborn period. Exome sequencing identified a hemizygous, missense variant in ZC4H2, NM_018684.4:c.196C>T p.(Leu66Phe), that affects the same amino acid residue as a previously reported, pathogenic ZC4H2 variant, c.197T>A p.(Leu66His). The variant was inherited from his mother, who had camptodactyly of the fifth fingers, and was also present in the maternal uncle who carried a diagnosis of cerebral palsy. The pathogenic missense variant in this family is located in the coiled-coil domain of the ZC4H2 protein. Although data remain scarce, missense variants in this domain may be associated with a milder, ZC4H2-associated rare disorder (ZARD) phenotype.